Perbandingan Kejadian Nyeri Tenggorok Paska Ekstubasi Akibat Penggunaan Pipa Endotrakea - Sally, Ruth (LeutikaPrio, 2014)
Background. One of the side effects of endotracheal intubation is sore throat due to trauma of the pharyngeal mucous caused by laryngoscopy and endotracheal cuff-pressure. One of some ways to reduce sore throat is to control intra-cuff pressure. Method. This study was carried out to compare incidence of post-extubation sore throat by measuring the cuff-pressure using manometer and palpation. This study was a double-blind randomized controlled trial at patients who underwent elective surgery with general anesthesia at GBST RSUP Dr. Sardjito Yogyakarta, male and female, 18-60 years old, physical status I and II. A hundred and fi fty patients were divided into 2 groups, each consisted 75 patients. Group A: cuff pressure 20 cmH2 O was measured by manometer, and group B: 20 cmH2 O was estimated by palpation. Cuff pressure measurement were done before extubation. Two subjects were dropped from this studyResult. There were no statistically signifi cant difference of sore throat after patients gain full consciousness, 2 hours post-operative in both groups (p>0,05), whereas 6 hours, 24 hours post operative procedures in both group were statistically signifi cant difference (p<0,05). From 10 subjects with sore throat, there were 13,3% in group A and 18 in group B (24,7%). There were 8 subjects with sore throat at 2 hours post-operation in group A (10,7%), and 16 subjects in group B (21,9%). The incidence of sore throat at 6 hours post-operation were 4 subjects in group A (5,3%), and 13 subjects in group B (17,8%). Lastly, for the sore throat reported at 24 hours post-operative procedures, there were 2 subjects in group A (2,7%), and 10 patients in group B (13,7%). Conclusion. The incidence of post-operative procedures sore throat in the group in which endotraceal tube cuff pressure were meassured by manometer lower than by palpation estimation.